A high-precision long-range cooperative radar system for gantry rail crane distance measurement. Issue 3 (4th March 2015) - Scheiblhofer, Werner; Scheiblhofer, Stefan; Schrattenecker, Jochen O.; Vogl, Simon; Stelzer, Andreas
Abstract : We present the implementation of a cooperative radar system on a gantry rail crane for distance measurements in an industrial environment. The measurement approach is based on the dual-ramp frequency-modulated continuous-wave principle, using identical sensor-nodes at the endpoints of the range of interest. Pseudo-range information is exchanged via a dedicated data-link between these stations. At the sensor-node a flexible high-performance signal processing and remote management engine is implemented. The system setup is controlled by a single host-PC, which is used as a man–machine interface for configuration of the remotely controlled measurement stations, system surveillance, and visualization of the measurement data. Indoor characterization of the developed hardware is sufficient for an efficient calibration of the system, minimizing distance offsets. On-site measurements at distances up to 1000 m with an accuracy better than 2 cm confirm the performance of the ranging system. Furthermore, the results are verified by simulation.